The life experiences of hypertension patients in participating tera gymnastics theraphy at rw 18 kelurahan padasuka in cimahi west java - Oop Ropei; Nida Handayani (STIKep PPNI Jawa Barat, 2021)
Aims : To explore the experience of hypertension sufferers in carry out tera gymnastics therapy at RW 18 Kelurahan Padasuka in Cimahi West Java. Methods : This research includes the type of qualitative research with phenomenology approach method. Participants were hypertensive patients who were participating tera gymnastics therapy. Using purposive sampling technique involving only 6 participants who carry out the Tera gymnastics activities. Purposive Sampling Method is a type of convenience sampling technique so that a saturation point of information will be achieved. Collecting data using indepth interviews using the researcher's herself as a research instrument. The interview process used semi structured questions and open ended questions. This research was equipped with a voice recorder in the form of a cellular phone and field notes to record non verbal responses. Results : It can be concluded that five main themes were identified are : (1) the condition of hypertension who experienced by the participants (2) The efforts when experiencing hypertension (3) the response during carry out tera exercise (4) the motivation in participating tera exercise (5) the expectations while hypertension suffering. Conclusions : The public can choose how to control hypertension with tera gymnastics therapy as a form of non pharmacological therapy